1981
DOI: 10.1139/v81-063
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of elsinochromes C and D. Pattern of acetate incorporation determined by 13C and 2H nmr

Abstract: Elsinochromes C and D have been isotopically labelled by supplementing cultures of the producing fungus with sodium [1-13C]-, [2-13C]-, [1,2-13C]-, or [2-13C, 2-2H3]acetate and the distribution of isotope has been determined by 13C and 2H nuclear magnetic resonance spectroscopy. The pattern of 13C labelling is consistent with assembly of the elsinochrome carbon skeleton from two heptaketide chains with loss of the terminal carboxyl groups, and dimerization to generate the 1,2-dihydrobenzo (ghi)-perylene ring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 4 publications
1
16
0
1
Order By: Relevance
“…No change in peak integration values was detected, indicating that the absence of label at methylene-derived carbons is more likely due to exchange at activated positions of enzyme-bound polyketide intermediates during mollisin biosynthesis. Similar examples of deuterium loss during the biosynthesis of other polyketide-pathway aromatic compounds from 2H-labeled acetate have been reported, and have been attributed to exchange of labile hydrogens in biosynthetic intermediates or in the product (10,11,15). The degree of *H retention at positions derived from the malonate methylene group appears to be quite unpredictable (14), and can vary from complete loss to almost complete retention (16).…”
Section: [Traduit Par La Revue]supporting
confidence: 60%
See 1 more Smart Citation
“…No change in peak integration values was detected, indicating that the absence of label at methylene-derived carbons is more likely due to exchange at activated positions of enzyme-bound polyketide intermediates during mollisin biosynthesis. Similar examples of deuterium loss during the biosynthesis of other polyketide-pathway aromatic compounds from 2H-labeled acetate have been reported, and have been attributed to exchange of labile hydrogens in biosynthetic intermediates or in the product (10,11,15). The degree of *H retention at positions derived from the malonate methylene group appears to be quite unpredictable (14), and can vary from complete loss to almost complete retention (16).…”
Section: [Traduit Par La Revue]supporting
confidence: 60%
“…The resonance displacements indicated that the three species were present in the proportions 2.5:2.7: 1.0 (error k0.3). A mixture of partidy and fully deuterated methyl groups has also been found in other fungal metabolites biosynthesized in the presence of ['H3]acetate (10)(11)(12). Activation of [2-2H3]-acetate to acetyl coenzyme A is not accompanied by exchange of deuterium with water, or with hydrogens at enzyme reaction centres (7).…”
Section: [Traduit Par La Revue]mentioning
confidence: 97%
“…fed radioisotope-labelled substrate revealed that elsinochromes are synthesized in a polyketide pathway by condensation of acetate and malonate monomers (Chen et al, 1966;Kurobane et al, 1981). To determine if any genes adjacent to EfPKS1 might also be involved in elsinochrome production in E. fawcettii, we carried out a DNA sequence analysis upstream and downstream of the EfPKS1 locus and identified nine new ORFs.…”
Section: Introductionmentioning
confidence: 99%
“…Elsinochrome D, probably derived from ‘C’ by the formation of a methylenedioxy ring, was identified and characterized from the pigment mixture of Elsinoë annonae Bitanc. and Jenkins (Kurobane et al ., 1981; Lousberg et al ., 1970b; Shirasugi and Misaki, 1992).…”
Section: Elsinochrome Pigments Produced By Elsinoë Speciesmentioning
confidence: 99%